In at the deep end - Matturi, Jenessi (Technical Centre for Agricultural and Rural Cooperation, 2006)
Born in Sierra Leone, Jenessi Matturi joined the Spore editorial team in October 1991. She works as a Project Assistant in CTA s Information Products and Services